2005
DOI: 10.2355/isijinternational.45.1138
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model for Removal of Inclusion in Molten Steel by Injecting Gas at Ladle Shroud

Abstract: A three-dimensional mathematical model has been developed to predict steady flow field, pressure distribution inside the shroud and efficiency of inclusion removal in tundish after argon gas injection at the shroud. Effects of the different opening of the slide gate and gas injection on velocity and pressure have been analyzed. The results show that the molten steel velocity gradually decreases and the pressure increases as the opening of the slide plane becomes larger. The velocity increases and the pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…The model could also be used to predict the gas and liquid flow conditions at which the transition from bubbly to churn-turbulent flow occurs. Wang et al 6) developed a mathematical model for inclusion removal in molten steel by inert gas shrouding. They discussed the probabilities of collisions and subsequent adhesion of bubbles with inclusions, and pointed out that bubble adhesion is an important parameter for inclusion removal.…”
Section: Introductionmentioning
confidence: 99%
“…The model could also be used to predict the gas and liquid flow conditions at which the transition from bubbly to churn-turbulent flow occurs. Wang et al 6) developed a mathematical model for inclusion removal in molten steel by inert gas shrouding. They discussed the probabilities of collisions and subsequent adhesion of bubbles with inclusions, and pointed out that bubble adhesion is an important parameter for inclusion removal.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 16) suggested a model for inclusion removal efficiency by gas bubbling under assumptions as follows.…”
Section: Resultsmentioning
confidence: 99%
“…According to Eqs. (14) and (15), the particle number density of the inflow is 38.4/ml. Thus, the RRI under different bubble conditions for a bare tundish are listed in Table 5.…”
Section: Particle Detection Of the Inlet Streammentioning
confidence: 99%
“…Some investigations [14][15][16] showed that the small inclusions which are non-wetted with the liquid can be brought to the top surface by attaching to gas bubbles, or by being captured within a rising bubble's wake. Besides, the upward flow caused by bubbles floating out of the bath, homogenizes liquid steel temperatures and composition.…”
Section: Removal Of Inclusions Using Micro-bubble Swarms In a Fourstrmentioning
confidence: 99%